GOOD CORPORATE GOVERNANCE (GCG) DALAM PERSPEKTIF MANAJEMEN SYARIAH DAN HUKUM ISLAM: GOOD CORPORATE GOVERNANCE (GCG) IN THE PERSPECTIVE OF SHARIA MANAGEMENT AND ISLAMIC LAW - Darmiati (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
Good Corporate Governance (GCG) is the principle of good corporate governance to create transparency, accountability, responsibility, independence, and fairness in the management of the organisation. In the context of Islamic economics, GCG principles are very much in line with sharia values, such as justice ('adl), trustworthiness, and accountability (mas'uliyyah). This article aims to examine the integration of the GCG concept with sharia management and Islamic law, and assess the extent to which these principles are internalised in Islamic financial institutions. The method used is a literature study with a qualitative approach. The results of the study show that the implementation of GCG within the sharia framework not only strengthens corporate governance, but also maintains spiritual and moral integrity in the Islamic business world.